In vitro antagonistic potential of Trichoderma sp. against Rhizoctonia solani under heavy metal stress - P.M. BHATTACHARYA, N. NONGMAITHEM, A. ROY* and (Indian Phytopathology, 2016)
Biocontrol potential of four isolates of Trichoderma sp. viz., MT-4, UBT-18, IBT-I and IBT-II were evaluated against R. solani under stress of nickel and cadmium. Dual culture experiment showed that exposure to metal gradient did not affect significantly the growth inhibition of R. solani by the test antagonist isolates. UBT-18 and IBT-II were found most potential isolates suppressing the mycelia growth of R. solani in dual culture under nickel and cadmium stress, respectively. Competitive parasitic survival exhibited that there was significant increase in colonization of sclerotia of R. solani by application of Trichoderma spp. irrespective of isolate concerned and exposure to metals’ gradient. No variation was found in parasitic survival of antagonist isolates on sclerotia at a given concentration of heavy metal. The test isolates reduced the growth of R. solani under nickel stress inspite of reduced volatile antibiotic production with highest production recorded in MT-4. Cadmium stress induced volatile antibiotic production with highest production by UBT 18. Although, growth of R. solani reduced with increased levels of nickel and cadmium, further inhibition of growth may be attributed to non-volatile antibiotic production by the antagonists. The highest non-volatile antibiosis was recorded by MT-4 and IBT-II under nickel and cadmium stress, respectively.